1994
DOI: 10.1038/bjc.1994.44
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic investigation of sporadic renal cell carcinoma: analysis of allele loss on chromosomes 3p, 5q, 11p, 17 and 22

Abstract: Summary To investigate the role of tumour-suppressor genes on the short arm of chromosome 3 in the mechanism of tumorigenesis in non-familial renal cell carcinoma, we analysed 55 paired blood-tumour DNA samples for allele loss on chromosome 3p and in the region of known or putative tumour-suppressor genes on chromosomes 5, 11, 17 and 22. Sixty-four per cent (35/55) of informative tumours showed loss of heterozygosity (LOH) of at least one locus on the short arm of chromosome 3, compared with only 13% at the p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 24 publications
1
59
1
1
Order By: Relevance
“…Interstitial deletion of chromosome 3p is one of the most common genetic rearrangements observed in tumour cells (Pandis et al, 1993). The region 3p14Ðp23 has been shown to be deleted in small-cell lung carcinomas (Petersen et al, 1997), non-small-cell lung carcinomas (Benachenhou et al, 1998b) renal cell carcinomas (Foster et al, 1994) and uterine cervical carcinomas (Kohno et al, 1993). In breast cancer, LOH ranging from 30% to 47% were observed at two separate regions, 3p13Ðp14 and 3p21Ðp25 (Chen et al, 1994) or 3p14.3Ðp21.1 and 3p24.3Ðp25.1 (Matsumoto et al, 1997), suggesting the involvement of several tumour-suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…Interstitial deletion of chromosome 3p is one of the most common genetic rearrangements observed in tumour cells (Pandis et al, 1993). The region 3p14Ðp23 has been shown to be deleted in small-cell lung carcinomas (Petersen et al, 1997), non-small-cell lung carcinomas (Benachenhou et al, 1998b) renal cell carcinomas (Foster et al, 1994) and uterine cervical carcinomas (Kohno et al, 1993). In breast cancer, LOH ranging from 30% to 47% were observed at two separate regions, 3p13Ðp14 and 3p21Ðp25 (Chen et al, 1994) or 3p14.3Ðp21.1 and 3p24.3Ðp25.1 (Matsumoto et al, 1997), suggesting the involvement of several tumour-suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…LOH at chromosome 5q22 has been described in 33% of renal cell tumours analysed by Southern hybridization (Morita et al, 1991). Applying microsatellites for allelotyping of nonpapillary RCCs, Foster et al (1994), Crossey et al (1994) and Trash-Bingham et al (1995) found LOH at chromosome 5q each in one out of 35, nine and 19 nonpapillary RCCs, respectively. Chromosome 5q21-22 region in involved in genetic changes of other types of cancer as well.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that these FARs carry one or several tumor suppressor genes (TSG) that contribute to the genesis of RCC when deleted (Latif et al, 1993;Van der Hout et al, 1991;Yamakawa et al, 1991;Bergerheim et al, 1989;Kovacs et al, 1988). Dierent studies de®ned dierent FARs in the short arm of chromosome 3, in 3p12 (Lubinski et al, 1994), in 3p13-p14 (Yamakawa et al, 1991;Lubinski et al, 1994), in 3p21 ( Van der Hout et al, 1991;Yamakawa et al, 1991), and in 3p25-pter (Foster et al, 1994), respectively. A recent analysis of sporadic RCCs has shown that 3p deletions most frequently (in 33 out of 44 analysed cases) included the 3p21 region between D3S643 and D3S1235 (Van den Berg et al, 1996a), i.e.…”
Section: Introductionmentioning
confidence: 99%